IDENTIFIKASI VARIABEL-VARIABEL PEMBANGUNAN LEMBAGA KPH KONSERVASI DI TN ALAS PURWO - Tri Atmojo; San Afri Awang; Erwan Agus Purwanto (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2014)
In Indonesia, most national parks have encountered several problems, such as conceptualization of national park, spatial conflicts, organizational management, and human resources, which need efforts to improve their management. Institutional transformations of national parks to the Conservation Forest Management Unit (FMU) are becoming an urgent issue. Evaluation on existing conditions of Alas Purwo National Park using the concept of institution-building and organizational theories is importance to evaluate organizational management of Alas Purwo National Park. This research aimed to provide data and explanation of the current state of institution-building variables in Conservation FMU of Alas Purwo National Park. The respondents were selected purposively from staff of Alas Purwo National Park. This study was conducted from November 2011 to May 2012. Using univariate analysis, the results indicated that the design of organization of Alas Purwo National Park was centralized and formal. The variable categories of transformational leadership, good forestry governance attitude, individual characteristics were high, good, and good, respectively. The research suggested to improve innovation in institutional establishment of Conservation FMU by increasing the quality of transformational leadership, good forestry governance attitude, and individual characteristics.